Pengelolaan Sampah Berbasis Masyarakat sebagai Strategi untuk Mendukung Destinasi Pariwisata Berkelanjutan: Studi Kasus Bank Sampah Tarhilala, Kabupaten Toba: PENGELOLAAN SAMPAH BERBASIS MASYARAKAT SEBAGAI STRATEGI UNTUK MENDUKUNG DESTINASI PARIWISATA BERKELANJUTAN: STUDI KASUS BANK SAMPAH TARHILALA, KABUPATEN TOBA - Ester Elisabeth Pardede (Journal of Applied Science in Tourism Destination, 2026)
Purpose : This study aims to analyze the implementation of community-based waste management through Bank Sampah Tarhilala and to examine its role in supporting sustainable tourism development in Toba Regency, part of Indonesia’s Lake Toba Super Priority Tourism Destination. The study also seeks to identify the environmental, social, and economic contributions of the waste bank, as well as the challenges that affect its effectiveness in the tourism context. Design/methodology/approach : This research employed a qualitative descriptive- analytical approach using a case study method. Data were collected through in-depth interviews with key informants, field observations, questionnaires, and documentation. The analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, supported by source and technique triangulation. Findings : The results indicate that Bank Sampah Tarhilala has implemented a systematic waste management process, including waste sorting, collection, processing, and distribution, supported by multi-stakeholder partnerships involving local government, tourism actors, private companies, and local communities. The waste bank manages an average of 7–8 tons of waste per month, contributing to a reduction in regional waste volume and improved environmental cleanliness in tourism areas around Lake Toba. In addition, the initiative supports circular economy practices, provides additional income opportunities for local communities, and enhances public awareness of sustainable waste management. Research limitations/implications : This study is limited by its qualitative approach and reliance on subjective perceptions of informants. Future research is recommended to apply quantitative or mixed-method approaches to measure financial performance and long-term impacts more comprehensively. Practically, the findings imply that strengthening institutional capacity, continuous environmental education,and cross-sector collaboration are essential to maximize the role of community-based waste banks in supporting sustainable tourism destinations. Keywords: Community-based waste management, waste bank, sustainable tourism, circular economy, Toba Regency